HUBUNGAN PENGETAHUAN IBU TENTANG PEMBERIAN MAKANAN DENGAN STATUS GIZI BALITA USIA 1-5 TAHUN DI POSYANDU PALUPI MUDA DESA SIDOREJO KECAMATAN JATISRONO KABUPATEN WONOGIRI - Rismawati; Siti Melati Indri Astuti (Jurnal Cakrawala Keperawatan, 2025)
Background: Mothers' knowledge of feeding toddlers aged 1 to 5 years in Sidorejo Village states that mothers do not know the appropriate feeding method for toddlers based on their age. In Sidorejo Village, 20 toddlers are in the malnourished category and 115 toddlers are in the normal/good nutrition category. A mother's understanding of food and nutrition for toddlers is important to be able to meet the nutritional needs of toddlers. Purpose of the study: To determine the relationship between maternal knowledge about feeding with the nutritional status of toddlers aged 1 to 5 years at the Palupi Muda Posyandu, Sidorejo Village, Jatisrono District, Wonogiri Regency. Method: The design of this study is quantitative descriptive research with a cross sectional approach. The number of samples of mothers and toddlers aged 1 to 5 years in September 2023 at the Palupi Muda Posyandu, Sidorejo Village, Jatisrono District, Wonogiri Regency is 60 people using total sampling. Data collection techniques with questionnaires while data analysis techniques use Mann Whitney U. The Results of the study : (1) Knowledge about infant feeding to toddlers at the Palupi Muda Posyandu, Sidorejo Village, Jatisrono District, mostly included in the good category of 20 people (40%); (2) Nutritional status in toddlers at Posyandu Palupi Muda Desa Sidorejo, Jatisrono District, most of which are 38 toddlers (76%) have good nutritional status; and (3) Test results with Mann Whitney you obtained a value of 51,000 (p value = 0.000 < 0.05) thus there is a relationship between the level of knowledge about infant feeding and nutritional status in toddlers at the Posyandu Palupi Muda Sidorejo Village, Jatisrono District. Conclusion: There is a relationship between the level of knowledge about infant feeding and nutritional status in toddlers at the Palupi Muda Posyandu, Sidorejo Village, Jatisrono District